PROTET PENGHAFAL AL-QUR'AN PADA SISWA SDIT KOTA LANGSA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN - Mulizar . (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
This paper discusses the process of memorizing the Koran which can improve students' ability to read the Koran. The purpose of this paper is to describe how the portrait of memorizing the Koran has a good influence on the ability to read the Koran in integrated Islamic schools in the city of Langsa. This paper is the result of a case study research using a descriptive analysis method with a qualitative approach, the main data sources are tests, observations and interviews, with supporting data sources in the form of important articles related to this theme. The results of this study explain that the process of implementing memorizing the Koran to improve the ability to read the Koran carried out by SDIT Langsa students is that students are divided into two levels, namely basic (Guidance) and intermediate (Tahsin). The students with basic level (guidance) get the memorization by listening (sima'i) from the teacher in class. The teacher mentally qinkan to students by repeating each verse that is read properly and correctly and followed by students several times, according to the target of memorizing verses per day, and it turns out that in general students are able to memorize the Koran by listening (sima'i). Meanwhile, students with intermediate level (tahsin), acquire memorization by using an independent memorization method.